Semi-empirical prediction of physical properties of (B3) TlP compound - Daoud, Salah; Bioud, Nadhira (International Journal of Physical Research, 2014)
The principal goal of this work is the prediction only by means of some emperical formulas and two other physical quantities (the bond length and the bulk modulus calculated initially from first-principle calculations) of the refractive index, the exciton Bohr parameter, the electronic polarizability, the plasmon energy, the force constants, the optical band gap energy, the homopolar and heteropolar energies, the bonding-antibonding energy gap, the ionicity, the dielectric constant, and the optical susceptibility of (B3) thallium phosphide (TlP) compound. In addition, the Debye temperature, the melting temperature, the thermal conductivity and finally the linear thermal expansion of this compound are also obtained. Our results are in general in good agreement with the previous results of the literature. Keywords: Optical Properties, Thermal Properties, TlP Compound.